Clinical activity of ASP8273 in Asian patients with non‐small‐cell lung cancer with EGFR activating and T790M mutations. Issue 9 (9th August 2018) - Murakami, Haruyasu; Nokihara, Hiroshi; Hayashi, Hidetoshi; Seto, Takashi; Park, Keunchil; Azuma, Koichi; Tsai, Chun‐Ming; Yang, James Chih‐Hsin; Nishio, Makoto; Kim, Sang‐We; Kiura, Katsuyuki; Inoue, Akira; et al.
Abstract : Epidermal growth factor receptor (EGFR)‐activating mutations confer sensitivity to tyrosine kinase inhibitor (TKI) treatment for non‐small‐cell lung cancer (NSCLC). ASP8273 is a highly specific, irreversible, once‐daily, oral, EGFR TKI that inhibits both activating and resistance mutations. This ASP8273 dose‐escalation/dose‐expansion study (NCT02192697) was undertaken in two phases. In phase I, Japanese patients (aged ≥20 years) with NSCLC previously treated with ≥1 EGFR TKI received escalating ASP8273 doses (25‐600 mg) to assess safety/tolerability and to determine the maximum tolerated dose (MTD) and/or the recommended phase II dose (RP2D) by the Bayesian Continual Reassessment Method. In phase II, adult patients with T790M‐positive NSCLC in Japan, Korea, and Taiwan received ASP8273 at RP2D to further assess safety/tolerability and determine antitumor activity, which was evaluated according to Simon's two‐stage design (threshold response = 30%, expected response = 50%, α = 0.05, β = 0.1). Overall, 121 (n = 45 [33W/12M] phase I, n = 76 [48W/28M]) phase 2) patients received ≥1 dose of ASP8273. In phase I, RP2D and MTD were established as 300 and 400 mg, respectively. As 27 of the 63 patients treated with ASP8273 300 mg achieved a clinical response, ASP8273 was determined to have antitumor activity. The overall response rate at week 24 in all patients was 42% (n = 32/76; 95% confidence interval, 30.9‐54.0). Median duration of progression‐free survival was 8.1 months (95% confidence interval, 5.6, upper bound not reached). The most commonly reported treatment‐related adverse event in phase II was diarrhea (57%, n = 43/76). ASP8273 300 mg was generally well tolerated and showed antitumor activity in Asian patients with both EGFR‐activating and T790M mutations. Abstract : This dose‐escalation/dose‐expansion study (NCT02192697) was carried out in two phases to assess the clinical activity of ASP8273 in Asian patients with non‐small‐cell lung cancer with epidermal growth factor receptor (EGFR)‐activating and T790M mutations. ASP8273 is a highly specific, irreversible, once‐daily, oral, EGFR tyrosine kinase inhibitor that inhibits both activating and resistance mutations. ASP8273 300 mg was generally well tolerated and showed antitumor activity in Asian patients with both EGFR‐activating and T790M mutations.